Effects of Inter-Stimulus Interval on Speech-Evoked Frequency-Following Response in Elderly Adults - Liu, Dongxin; Hu, Jiong; Dong, Ruijuan; Chen, Jing; Musacchia, Gabriella; Wang, Shuo (Frontiers in Aging Neuroscience, 2018)
Background: The speech-evoked frequency following response (FFR) has shown to be useful in assessing complex auditory processing abilities and in different age groups. While many aspects of FFR have been studied extensively, the effect of timing, as measured by inter-stimulus-interval (ISI), especially in the older adult population, has yet to be thoroughly investigated. Objective: The purpose of this study was to examine the effects of different ISIs on speech evoked FFR in older and younger adults who speak a tonal language, and to investigate whether the older adults’ FFR were more susceptible to the change in ISI. Materials and Methods: Twenty-two normal hearing participants were recruited in our study, including 11 young adult participants and 11 elderly participants. An Intelligent Hearing Systems Smart EP evoke potential system was used to record the FFR in four ISI conditions (40, 80, 120 and 160 ms). A recorded natural speech token with a falling tone /yi/ was used as the stimulus. Two indices, stimulus-to-response correlation coefficient and pitch strength, were used to quantify the FFR responses. Two-way analysis of variance (ANOVA) was used to analyze the differences in different age groups and different ISI conditions. Results: There was no significant difference in stimulus-to-response correlation coefficient and pitch strength among the different ISI conditions, in either age groups. Older adults appeared to have weaker FFR for all ISI conditions when compared to their younger adult counterparts. Conclusion: Shorter ISIs did not result in worse FFRs from older adults or younger adults. For speech-evoked FFR using a recorded natural speech token that is 250 ms in length, an ISI of as short as 40 ms appeared to be sufficient and effective to record FFR for elderly adults.